The Capacitive Resistivity Technique for Electrical Imaging of the Shallow Subsurface - Kuras, Oliver (2002)
Capacitive resistivity (CR) is a novel geophysical technique for the non-intrusive characterisation of the shallow subsurface by electrical imaging. CR is capable of extending the scope of the conventional DC resistivity technique to the urban built environment and other settings where galvanic contact cannot be achieved or where high contact impedances result in poor data quality. Fundamentally, the CR technique is based upon the concept of capacitive coupling between sensors and the ground and a generalisation of the DC four-point array for measuring the resistivity of the subsurface at frequencies in the VLF range. This thesis provides a unified description of CR, including its physical principles, their theoretical formulation and practical implementation in geophysical instruments. In general, the transfer impedance across a capacitive array is a complex function of frequency and geometry. It is shown that a low induction number mode of operation exists where resistivity is proportional to the in-phase component of the transfer impedance. The quadrature component is generally sensitive to a combination of parameters including sensor elevation, dipole offset and ground resistivity. Under the low induction number regime, the electric field is quasi-stationary so that theoretical equivalence with the DC case is achieved and conventional DC interpretation schemes are applicable to CR data.